The Relationship between Primordial Images and Formal Symbols in Improvisational Painting, Case Study: Monavar Ramazani's Paintings - Fereshteh Paidar Nobakht; ali abbasi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This study aims to investigate the ways in which the structures of human imagination have connections with primordial forms and symbols and shows how these early spontaneous images in humans transform such symbols into thoughts and artistic productions. It seems that human imagination is structured by generic forms based on ancient legends and myths. These forms have been systematized in the Nocturnal regime of imagination introduced by Gilbert Durand. Durand considers the structure of human imagination as a dynamic regime in a way that it can reveal primordial images with the help of symbols. This regime can reveal the relationship between human beings and cultures with the help of symbolic imagination. Monavar Ramazani's paintings are forms of imagination rooted in religious narratives, folk tales and oral literatures of her childhood. She has noted that she had first seen some of her paintings in her dreams before she started to paint them. The results of this study show that even though these painting aspire to be cultural images, they reveal a deep and symbolic connection with archetypes